An Evidence‐Based Forensic Taxonomy of Windows Phone Communication Apps. Issue 3 (17th August 2017) - Cahyani, Niken Dwi Wahyu; Martini, Ben; Choo, Kim‐Kwang Raymond; Ab Rahman, Nurul Hidayah; Ashman, Helen
Abstract: Communication apps can be an important source of evidence in a forensic investigation (e.g., in the investigation of a drug trafficking or terrorism case where the communications apps were used by the accused persons during the transactions or planning activities). This study presents the first evidence‐based forensic taxonomy of Windows Phone communication apps, using an existing two‐dimensional Android forensic taxonomy as a baseline. Specifically, 30 Windows Phone communication apps, including Instant Messaging ( IM ) and Voice over IP ( VoIP ) apps, are examined. Artifacts extracted using physical acquisition are analyzed, and seven digital evidence objects of forensic interest are identified, namely: Call Log, Chats, Contacts, Locations, Installed Applications, SMSs and User Accounts . Findings from this study would help to facilitate timely and effective forensic investigations involving Windows Phone communication apps.